The Role of Ferroptosis in Cardiovascular Disease and Its Therapeutic Significance - Chen, Zhenzhen; Yan, Youyou; Qi, Chao; Liu, Jia; Li, Longbo; Wang, Junnan (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases (CVDs) are the leading cause of deaths worldwide with regulated cell death playing an important role in cardiac pathophysiology. However, the classical mode of cell death cannot fully explain the occurrence and development of heart disease. In recent years, much research has been performed on ferroptosis, a new type of cell death that causes cell damage and contributes to the development of atherosclerosis, myocardial infarction, heart failure, and other diseases. In this review, we discuss the role of different organelles in ferroptosis and also focus on the relationship between autophagy and ferroptosis. Additionally, we describe the specific mechanism by which ferroptosis contributes to the development of CVD. Finally, we summarize the current research on ferroptosis-related pathway inhibitors and the applications of clinically beneficial cardiovascular drugs.